2016
DOI: 10.1016/j.concog.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Mental body representations retain homuncular shape distortions: Evidence from Weber’s illusion

Abstract: 2 Highlights We compared the shape of body part representations underlying Weber's illusion. We found that the represented shape of both the arm and hand was highly distorted. The shape of the arm representation was more distorted than the hand. Mental body representations retain shape distortions characterizing the somatosensory homunculus. 3 AbstractMental body representations underlying tactile perception do not accurately reflect the body's true morphology. For example, perceived tactile distance is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 37 publications
4
55
2
Order By: Relevance
“…For example, Weber (1834Weber ( /1996 found that the perceived distance between two points of a compass changed as he moved them across his skin, feeling farther apart on regions of high tactile sensitivity compared to regions of lower sensitivity. Subsequent studies have replicated this pattern and suggest a systematic relation between perceived tactile distance and the spatial sensitivity of skin surfaces (e.g., Cholewiak, 1999;Taylor-Clarke et al, 2004;Anema, Wolswijk, Ruis, & Dijkerman, 2008;Miller, Longo, & Saygin, 2016), an effect known as Weber's illusion, suggesting that tactile distance perception preserves spatial distortions characteristic of the famous 'Penfield homunculus' (Penfield & Boldrey, 1937).…”
Section: Distortions Of Tactile Distance Perceptionmentioning
confidence: 88%
“…For example, Weber (1834Weber ( /1996 found that the perceived distance between two points of a compass changed as he moved them across his skin, feeling farther apart on regions of high tactile sensitivity compared to regions of lower sensitivity. Subsequent studies have replicated this pattern and suggest a systematic relation between perceived tactile distance and the spatial sensitivity of skin surfaces (e.g., Cholewiak, 1999;Taylor-Clarke et al, 2004;Anema, Wolswijk, Ruis, & Dijkerman, 2008;Miller, Longo, & Saygin, 2016), an effect known as Weber's illusion, suggesting that tactile distance perception preserves spatial distortions characteristic of the famous 'Penfield homunculus' (Penfield & Boldrey, 1937).…”
Section: Distortions Of Tactile Distance Perceptionmentioning
confidence: 88%
“…In the case of tactile distance perception, however, there is also evidence that this perceptual anisotropy is even bigger on the forearm than on the hand (Le Cornu Knight et al, 2014; Miller et al, 2016). The current study did not find any evidence for differences between these body parts, with quite similar distortions apparent in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Weber (1834/1996) in his classic studies on touch found that as he moved the two points of a compass across his skin, it felt like the distance between the two points increased as he moved them from a region or relatively low spatial sensitivity (e.g., the upper arm) to a region of higher sensitivity (e.g., the palm). Subsequent studies have replicated this general pattern, showing that perceived tactile distances appear to be systematically related to the sensitivity of different skin surfaces (e.g., Goudge, 1918; Marks et al, 1982; Cholewiak, 1999; Taylor-Clarke et al, 2004; Anema et al, 2008; Miller et al, 2016). Similarly, large anisotropies of perceived tactile distance have been reported on the limbs, with stimuli oriented across the width of limbs being perceived as substantially farther apart than stimuli oriented along the length of the limbs (Green, 1982; Longo and Haggard, 2011; Canzoneri et al, 2013; Longo and Sadibolova, 2013; Le Cornu Knight et al, 2014; Miller et al, 2014, 2016; Longo, 2015).…”
Section: Introductionmentioning
confidence: 88%